A PTHrP-2 loaded adhesive cellulose acetate nanofiber mat as wound dressing accelerates wound healing - Ang Li (Elsevier, 2021)
Although various dressings currently used have the effect of promoting wound healing, they still cannot meet the requirements of clinically efficient treatment. Recently, parathyroid hormone (PTH) and its pathway have been shown as the new target for wound repair. However, using PTH in clinical wound treatment can be a question. This study is to develop a novel PTHrP-2 loaded cellulose acetate nanofiber mat (CAP) via electrospinning to benefit wound repair. By observing the effects of prepared CAP on cell proliferation, migration, tube formation, and wound healing in the rat models, we have evaluated the safety and effectiveness of CAP. With the extract of CAP, the viability of human umbilical vein endothelial cells and fibroblasts was enhanced. It also could significantly increase the movement rate of human umbilical vein endothelial cells and promote tube formation. The wound closure speed of CAP treatment was significantly faster than the cellulose acetate group. In conclusion, CAP has a promoting effect in angiogenesis, collagen formation and re-epithelialization, thereby it can accelerate wound healing. CAP is a promising translational nanocomposite material, which might be transferred into a new type of wound dressing.